If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -26 + x = 3x + 22 Reorder the terms: -26 + x = 22 + 3x Solving -26 + x = 22 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -26 + x + -3x = 22 + 3x + -3x Combine like terms: x + -3x = -2x -26 + -2x = 22 + 3x + -3x Combine like terms: 3x + -3x = 0 -26 + -2x = 22 + 0 -26 + -2x = 22 Add '26' to each side of the equation. -26 + 26 + -2x = 22 + 26 Combine like terms: -26 + 26 = 0 0 + -2x = 22 + 26 -2x = 22 + 26 Combine like terms: 22 + 26 = 48 -2x = 48 Divide each side by '-2'. x = -24 Simplifying x = -24
| -6+2(2x+13)=48 | | .1x=.2(x) | | 18.08-23.37x=27/2.43x+4.2 | | -9x+3(5-10x)= | | 2(x+1)=2 | | 98=-7(-4-2x) | | -8x+87=103 | | 3b-2b=-7-b-5b | | -0.3p-2.1=-3.6 | | 5(2)=-4y+4y | | 6(0.33h+1)= | | -10(2n-1)+7n= | | 8x+4=12x-16 | | 5x/4=30 | | -32-3x=76-7x | | r^2-7rf+12f^2=0 | | x^2(x^2-25)-49(x^2-25)=0 | | X/-2-2=10 | | 2-9[3-(5y-9)]= | | 5/2-x/5=7/10 | | x^2=y+2 | | -8+3x=2(x-5) | | 4-0.4(3d-5)=12 | | (8x^10y^13)/(-4x^7y^6) | | a+b/3=c | | -380=8m-6(-7m+5) | | 5(1)=-4y+4y | | s^2+11sf+28f^2=0 | | 4-0.4(4d-5)=12 | | 750-50x=35.00x-185 | | 5c^3+5c^2-100c=0 | | (4x)/6-(2-3x)/8=(7x+8)/12 |